PENGARUH KARAKTERISTIK DAERAH, KOMPLEKSITAS, DAN TEMUAN AUDIT TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA LKPD KABUPATEN/KOTA DI PROVINSI SUMATERA UTARA TAHUN 2013-2017) - Pratiwi Gita Ayunda; Taufik Taufeni; Odiatma Fajar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of age of government, size ofgovernment, OPD, legislature size, and audit finding on level of financialstatement discosure in Sumatera Utara Province. The population in this studywere local government financial report in Sumatera Utara Province 2013-2017.The sample used amounted to 115 financial reports who were selected through apurposive sampling method. The method used in this study is multiple linearregression analysis by using Statistical Product and Service Solution (SPSS)version 23.0. The result of this study indicate that: (1) age of government has aneffects on the level of financial statement disclosures with a significant level of0,000 < 0,05, (2) size of legislature has an effects on the level of financialstatement disclosures with a significant level of 0,005 < 0,05, (3) OPD does noteffect on the level of financial statement disclosures with significant level of 0,650< 0,05, (4) legislature size does not effect on the level of financial statementdisclosures with a significant level of 0,258 > 0,05, (5) audit finding has an effectson the level of financial statement disclosures with a significant level 0,003 <0,05. Overall, it is known that all of independence variabels have an effect on thelevel of financial statement disclosures of 42,9 %. While 57,1 % is influenced byother variabels not examined in this study.Keywords : Disclosure level, age of government , Size of government, OPD,legislature size, audit finding.